PENERAPAN METODE SCRAMBLE BERBASIS PERMAINAN TEKOSILANG UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INDONESIA SISWA KELAS II DI SDN CIPINANG BESAR UTARA 08 PAGI JAKARTA TIMUR - Leander, Bella; Robiatul Munajah (Journal of Practice Learning and Educational Development, 2026)
This study aimed to improve second-grade students Indonesian vocabulary mastery through the implementation of the scramble method based on crossword games. Vocabulary mastery is a fundamental component that supports language skills and reading literacy in elementary school students. This research employed classroom action research using the Kemmis and McTaggart model, conducted in two cycles. The research participant were 24 second-grade students at a public elementary school in East Jakarta. Data werw collected through vocabulary mastery tests, classroom observation and documentation. Quantitative data were analyzed descriptively by calculating mean scores and learning mastery percentages, while qualitative data were analyzed through data reduction and interpretation of observation results. The findings revealed a gradual improvement in students vocabulary mastery across each cycle. Both the average scores and mastery levels increased after the implementation of the scramble method integrated with crossword games. These results indicate that the scramble method combined with crossword games effectively promotes active, engaging, and meaningful learning experiences, thereby enhancing Indonesian vocabulary mastery among second-grade elementary school students.